Markets and marketing research on poverty and its alleviation: Summarizing an evolving logic toward human capabilities, well-being goals and transformation. (September 2017) - Sridharan, Srinivas; Barrington, Dani J.; Saunders, Stephen G.
Marketing practitioners and business scholars now view some of the world's poorest communities as profitable growth markets. Hence a market-based approach to poverty alleviation has gathered momentum. This article traces the evolution of such a market-based approach over four decades and highlights a gradual trend away from a deficit-reduction approach (focused on constraints and justice) towards an opportunity-expansion approach (focused on capabilities and well-being). This trend is summarized in an analytical framework of human capabilities, well-being goals and transformative impact evolved from the literature. The framework is then used to analyse the practice of sanitation marketing, which has emerged as a key method in one of the highest priority domains in international development discourse – sanitation. The article concludes with a discussion of how contemporary work can further take forward the key tenets of the framework and guide the development of 'good markets' for the poor.